Malaysia case studies of urban and regional planning - Mohamed Osman, Mariana (IIUM Press, 2015)
Malaysia Case Studies of Urban and Regional Planning is another continued effort by academicians from the Kulliyyah of Architecture and Environmental Design (KAED) of the International Islamic University Malaysia (IIUM) in sharing their research outputs with the decision-makers, practitioners, stakeholders, students of built environment as well as interested members of the public. Cities in Malaysia are increasingly faced by ever changing development. Nowadays, the concept of urban and urbanism in regards to problems such as increasing population, multiplicity in number of cities, air and noise pollution and traffic jams evolved in deep variation and changes. It is obvious that rapid changes in physical and economic development joint with social changes will have an influence on live dynamic of cities.